FAULT SEGMENTATION OF SOUTHERN SUMATRA (SIANOK SEGMENT-SEMANGKO SEGMENT) BASED ON ACTIVE FAULT MAPPING THROUGH DIGITAL ELEVATION MODEL (DEM) AND SEISMICITY - FALAH, MUHAMMAD FAZRUL; Mukti, Muhammad Ma'ruf; Ismawan, Ismawan; Helmi, Faisal (Faculty of Geological Engineering, Universitas Padjadjaran, 2023)
Subduction with oblique dimensions causes the formation of structures in the Sumatra area, one of which is the formation of the Sumatran Fault System with dextral fault movements. Strike-slip Fault are segmented in varying geometries and sizes. The Sumatran Fault has been extensively segmented through geometric and structural analysis on the surface and seismic analysis using seismic clusters. This research was conducted to update fault segmentation using surface structure analysis and earthquake data distribution. Surface mapping was carried out through DEM imagery and association with earthquakes and their focal mechanisms, as well as geological factors such as lithology and volcanoes related to the Sumatra Fault. There were 14 segments based on geological and structural identification such as step over, bend, and discontinuity (gap). All the active fault in the region can produce >Mw 6.6 earthquake.